2006
DOI: 10.1371/journal.pctr.0010021
|View full text |Cite|
|
Sign up to set email alerts
|

Volume Expansion with Albumin Compared to Gelofusine in Children with Severe Malaria: Results of a Controlled Trial

Abstract: Objectives:Previous studies have shown that in children with severe malaria, resuscitation with albumin infusion results in a lower mortality than resuscitation with saline infusion. Whether the apparent benefit of albumin is due solely to its colloidal properties, and thus might also be achieved with other synthetic colloids, or due to the many other unique physiological properties of albumin is unknown. As albumin is costly and not readily available in Africa, examination of more affordable colloids is warra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 40 publications
2
82
0
3
Order By: Relevance
“…The participants in the trial were therefore comparable to study cohorts enrolled in our previous fluid resuscitation trials [3,15,19], with one exception [16].…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…The participants in the trial were therefore comparable to study cohorts enrolled in our previous fluid resuscitation trials [3,15,19], with one exception [16].…”
Section: Participantsmentioning
confidence: 99%
“…We aimed to recruit 80 children: 40 to receive Dextran and 40 to receive HES which would give sufficient data on the frequency of serious adverse events and clinical data on correction of hypovolaemic shock. Our previous experience suggested that this number was sufficient to provide information on these key endpoints [3,10,15,16]. Additional new data generated by the study included bolus volumes required of Dextran and HES to achieve satisfactory improvements in haemodynamic features of shock (primary endpoint).…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Some of the factors that may be related to the outcome in that particular group of patients include: high rates of malaria; significant anemia; lack of identification of pathogens in the majority of the patients (only 12 % had positive blood cultures and there were no other tests for bacterial or viral pathogens); lack of availability of respiratory support (ventilation was not available, and in some cases access to oxygen was extremely limited). The result was particularly surprising in light of previous studies from that region demonstrating improvements in patients with severe malaria treated with fluid boluses [74,75]. It is relevant that although early antibiotic administration, vigorous volume resuscitation, and early use of inotropic support was associated with a dramatic improvement in outcomes from severe meningococcal disease in the UK [76], early endotracheal intubation and ventilation was provided for these patients.…”
Section: Fluid Resuscitationmentioning
confidence: 96%